The Impact of the Whole Language Approach Towards Children Early Reading and Writing in English - Fauzi, Chandra; Basikin (Program Studi Magister Pendidikan Anak Usia Dini, 2020)
This study aims to determine the effect of the whole language approach to the ability to read and write in English in early stages of children aged 5-6 years in one of the kindergartens in the Yogyakarta Special Region. The population in this study were 43 children who were in the age range of 5-6 years in the kindergarten. Twenty-nine participants were included in the experimental class subjects as well as the control class with posttest only control group design. Observation is a way to record data in research on early reading and writing ability. The results of Multivariate Anal- ysis of Covariance (Manova) to the data shows that 1) there is a difference in ability between the application of the whole language approach and the conventional approach to the ability to read the beginning of English; 2) there is a difference in ability between applying a whole language approach and a conventional approach to writing English beginning skills; 3) there is a difference in ability between the whole language approach and the conventional approach to the ability to read and write the beginning in English Keywords: Whole language approach, Early reading, Early writing, Early childhood Reference Abdurrahman, M. (2003). Pendidikan bagi Anak Berkesulitan Belajar. Jakarta: Rineka Cipta. Aisyah, S., Yarmi, G., & Bintoro, T. (2018). Pendekatan Whole Language dalam Pengembangan Kemampuan Membaca Permulaan Siswa Sekolah Dasar. Prosiding Seminar Nasional Pendidikan, 160–163. Alhaddad, A. S. (2014). Joedanian Literacy Education Should Whole Language be Implemented? European Scientific Journal, 10(8). Aulina, C. N., & Rezania, V. (2013). Metode Whole Language untuk Pembelajaran Bahasa Pada Anak TK. Pendidikan Usia Dini. Austring, B. D., & Sørensen, M. (2012). A Scandinavian View on the Aesthetics as a Learning Media. Journal of Modern Education Review, 2(2), 90–101. Cahyani, H., Courcy, M. de, & Barnett, J. (2018). Teachers’ code-switching in bilingual classrooms: exploring pedagogical and sociocultural functions. International Journal of Bilingual Education and Bilingualism, 21(4), 465–479. Cahyani, W. A. (2019). Pengembangan Model Pembelajaran Membaca pada Anak Usia Dini. Universitas Negeri Yogyakarta. CCSU NEWS. (2019). World’s Most Literate Nations Ranked. In WORLD’S MOST LITERATE NATIONS RANKED. Chodidjah, I. (2007). Teacher training for low proficiency level primary English language teachers: How it is working in Indonesia. In British Council (Ed.) Primary Innovations: A Collection of Papers, 87–94. Crystal, D. (2003). The Cambridge Encyclopedia of the English Language (second Edi). Cambridge: Cambridge University Press. Dhieni, N., Fridani, L., Muis, A., & Yarmi, G. (2014). Metode Perkembangan Bahasa. Universitas Terbuka, 1(155.4), 1–28. Dixon, J., & Sumon, T. (1996). Whole Language: An Integrated Approach to Reading and Writing. Action-Learning Manuals for Adult Literacy, 4. Doman, G. (1985). Ajaklah Balita Anda Belajar Meembaca. Bandung: CV. Yrama Widya. Fat, N. (2015). Ranking Minat Baca Pelajar Indonesia. In Minat Baca Indonesia. Flores, N. (2013). Undoing Truth in Language Teaching: Toward a Paradigm of Linguistic Aesthetics. Working Papers in Educational Linguistics (WPEL), 28(2). Folkmann, M. N. (2010). Evaluating aesthetics in design: A phenomenological approach. The MIT Press, 26(1), 40–53. Froese, V. (1991). Whole Language Practice and Theory. Boston: Allyn and Bacon.Gagne, R. M., & Briggs, L. J. (1996). Principle of Instructional Design. New York: Richard and Winston.Gardner, H. (2013). Multiple Intelegences : The Theory in ractice a Reader. New York: Basic. Goodman, K. (1986). What‟s whole in whole language. Portsmouth: NH: Heinemann. Goodman, K. S. (1986). What’s Whole in Whole Language? A Parent/Teacher Guide to Children’s Learning. Heinemann Educational Books, Inc: 70 Court St., Portsmouth, NH 03801. Hammerby, H. (1982). Synthesis in Second Language Teaching. Blane: Second Language. Hardinansyah, V. (2017). Analisis Kebutuhan pada Pengajaran Bahasa Inggris di PG-PAUD. Jurnal Pendidikan Dan Pembelajaran Anak Usia Dini, 4(2), 92–102. Jamaris, M. (2006). Perkembangan dan Pengembangan Anak Usia Dini Taman Kanak-kanak. Jakarta: Gramedia Widiasarana. Krashen, S. D. (1981). Second Language Acquisition and Second Language Learning (Wesley Longman Ltd, ed.). Addison. Krashen, S., Long, M. H., & Scarcella, R. (1979). Accounting for child-adult differences in second language rate and attainment. TESOL Quarterly, 13, 573-82. Ling-Ying, & Huang. (2014). Learning to Read with the Whole Language Approach: The Teacher’s View. Canadian Center of Science and Education : English Language Teaching, 5(7). Ling, P. (2012). The “Whole Language” Theory and Its Application to the Teaching of English Reading. Journal of Canadian Center of Science and Education, 5(3). Maulidia, C. R., Fadillah, & Miranda, D. (2019). Pengaruh Pendekatan Whole Language Terhadap Kemampuan Membaca 5-6 Tahun di TK Mawar Khatulistiwa. Program Studi Pendidikan Guru PAUD FKIP Untan Pontianak, 8(7). Mayuni, I., & Akhadiah, S. (2016). Whole Language-Based English Reading Materials. International Journal of Applied Linguistics & English Literature, 5(3). Meha, N., & Roshonah, A. F. (2014). Implementasi Whole Language Approach sebagai Pengembangan Model Pembelajaran Berbahasa Awal Anak Usia 5-6 Tahun di PAUD Non Formal. Jurnal Pendidikan, 15(1), 68–82. Moats, L. (2007). Whole language high jinks: How to Tell When “Scientifically-Based Reading Instruction” Isn’t. Washington: Thomas B. Fordham Institute. Montessori, D. M. (1991). The discovery of the Child. New York: Ballatine Books.Morrow, L. M. (1993). Literacy Development in the Early Years. United States of America: Allyn & Bacon.Munandar, A. (2013). Pemakaian Bahasa Jawa Dalam Situasi Kontak Bahasa di Daerah Istimewa Yogyakarta. Jurnal Sastra Inggris, 25(1), 92–102. Musfiroh, T. (2009). Menumbuhkembangkan Baca-Tulis Anak Usia Dini. Yogyakarta: Grasindo. Nirwana. (2015). Peningkatan Kemampuan Membaca Cepat Melalui Pendekatan Whole Language pada Siswa Kelas VI SD Negeri 246 Bulu-Bulu Kecamatan Tonra Kabupaten Bone. Jurnal Onoma: Pendidikan, Bahasa, Dan Sastra, 1(1), 79-94., 1(1), 79–94. Novitasari, D. R. (2010). Pembangunan Media Pembelajaran Bahasa Inggris Untuk Siswa Kelas 1 Pada Sekolah Dasar Negeri 15 Sragen. Sentra Penelitian Engineering Dan Edukas, Volume 2 N. Oladele, A. O., & Oladele, I. T. (2016). Effectiveness of Collaborative Strategic Reading and Whole Language Approach on Reading Comprehension Performance of Children with Learning Disabilities in Oyo State Nigeria Adetoun. International Journal on Language, Literature and Culture in Education, 3(1), 1–24. Olusegun, B. S. (2015). Constructivism Learning Theory: A Paradigm for Teaching and Learning. Journal of Research & Method in Education, 5(6), 66–70. Ortega, L. (2009). Understanding Second Language Acquisition. New York: Routledge.Otto, B. (2015). Perkembangan Bahasa Pada Anak Usia DIni (third Edit). Jakarta: Prenadamedia. Papalia, D., Old, S., & Feldman, R. (2008). Human Development (Psikologi Perkembangan). Jakarta: Kencana. Papalia, Old, & Feldman. (2009). Human Development (Psikologi Perkembangan (Kesembilan). Jakarta: Kencana. Pellini, A. PISA worldwide ranking; Indonesia’s PISA results show need to use education resources more efficiently. , (2016). Phakiti, A. (2014). Experimental Research Methods in Language Learning. London: Bloomsbury Academic. Rahim, F. (2015). Pengajaran Bahasa di Sekolah Dasar. Jakarta: PT Bumi Aksara. Routman, R. (2014). Read, write, lead: Breakthrough strategies for schoolwide literacy success. Sadtono, E. (2007). A concise history of TEFL in Indonesia. English Education in Asia: History and Policies, 205–234. Sani, R.A. (2013). Inovasi Pembelajaran. Jakarta: Bumi Aksara.Sani, Ridwan A. (2013). Inovasi Pembelajaran. Jakarta: PT Bumi Aksara. Santrock, J. W. (2016). Children (Thirteenth). New York: McGraw-Hill Education. Saracho, O. N. (2017). Literacy and language: new developments in research, theory, and practice. Early Childhood Development and Care, 3(4), 187. https://doi.org/10.1080/03004430.2017.1282235 Semiawan, C. R. (1983). Memupuk Bakat dan Minat Kreativitas Siswa Sekolah Menengah. Jakarta: Gramedia Pustaka Utama. Sikki, E. A. A., Rahman, A., Hamra, A., & Noni, N. (2013). The Competence of Primary School English Teachers in Indonesia. Journal of Education and Practice, 4(11), 139–146. Siskandar. (2009). Kurikulum Berbasis Kompetensi. Jakarta: Fasilitator. Solchan, T. W., Mulyati, Y., Syarif, M., Yunus, M., Werdiningsih, E., Pramuki, B. E., & Setiawati, L. (2008). Pendidikan Bahasa Indonesia di SD. Jakarta. Jakarta: Universitas Terbuka. Solehudin, O. (2007). Model Pembelajaran Membaca Reading Workshop: Studi Kuasi Eksperimen di SD Muhammadiyah VII Bandung (Doctoral dissertation, Universitas Pendidikan Indonesia). Universitas Pendidikan Indonesia. Suparno, S., & Yunus, M. (2007). Keterampilan Dasar Menulis. Jakarta: Universitas Terbuka. Susanto, A. (2011). Perkembangan Anak Usia Dini Pengantar dalam Berbagai Aspeknya. Jakarta: Kencana Prenada Media Group. Suyanto, K. K. E. (2010). Teaching English as foreign language to young learners. Jakarta: State University of Malang. Tarigan, D. (2001). Pendidikan Bahasa dan sastra Indonesia Kelas Rendah. Jakarta: Universitas Terbuka. Trask, R. L., & Trask, R. L. (1996). Historical linguistics. New York: Oxford University Press. Ur, P. (1996). A course in Language Teaching. Practice and Theory. Cambridge: Cambridge. University Press. Williams, A. L., McLeod, S., & McCauley, R. J. (2010). Interventions for Speech Sound Disorders in Children. Brookes Publishing Company.: PO Box 10624; Baltimore; MD 21285. Wright, P., Wallance, J., & McCAarthy, J. (2008). Aesthetics and experience-centered design. ACM Transactions on Computer-Human Interaction (TOCHI), 15(4), 18.